Pemanfaatan Media Pembelajaran IPAS Dengan Model Addie Dalam Materi Sistem Pernapasan Kelas V - Apriningrum, Cindy Oktavia Dea; Samsudin, Samsudin (Social Science Academic, 2024)
The use of learning media while teaching is still rarely used in schools. In general, this media can be used as a means of transforming knowledge. It is often found that teaching teachers only has the lecture method and brings LKS books, especially in science subjects. These subjects must be really practiced so that the shadow of students is not abstract. So this needs to be updated in the learning media used. Therefore, media development is needed for teachers so that they can help students understand the respiratory system in humans. The purpose of this study is to create and develop learning media on class V respiratory system material at MI Tahfidzul Qur'an Nurul Iman. This research uses qualitative methods with the ADDIE model (analyze, design, development, implementation, and evaluation). The results of the research obtained are that students become more aware of how the respiratory process in humans is assisted by using learning media that they have made in groups.